2014
DOI: 10.1021/bi501183x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Phenylalanine Hydroxylase by Phenylalanine Does Not Require Binding in the Active Site

Abstract: Phenylalanine hydroxylase (PheH), a liver enzyme that catalyzes the hydroxylation of excess phenylalanine in the diet to tyrosine, is activated by phenylalanine. The lack of activity at low levels of phenylalanine has been attributed to the N-terminus of the protein’s regulatory domain acting as an inhibitory peptide by blocking substrate access to the active site. The location of the site at which phenylalanine binds to activate the enzyme is unknown, and both the active site in the catalytic domain and a sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…2B, colored circles in inset). The mid-point of the transition for the PheH R270K mutant is shifted relative to the wild-type enzyme, occurring at a [L-Phe] of 370 ± 35 μ M. A similar shift was previously observed by tryptophan fluorescence measurements of the same construct 26 . As a superposition of our PheH Δ24 R270K and wt-PheH structures shows no significant change beyond the immediate vicinity of the mutation (Fig.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…2B, colored circles in inset). The mid-point of the transition for the PheH R270K mutant is shifted relative to the wild-type enzyme, occurring at a [L-Phe] of 370 ± 35 μ M. A similar shift was previously observed by tryptophan fluorescence measurements of the same construct 26 . As a superposition of our PheH Δ24 R270K and wt-PheH structures shows no significant change beyond the immediate vicinity of the mutation (Fig.…”
Section: Resultssupporting
confidence: 84%
“…First, the allosteric binding site for L-Phe was shown by mutagenesis and fluorescence quenching to be distinct from the active site. 26 In this study, an R270K mutation, which has been associated with PKU in humans, 27 was shown to abolish L-Phe binding in the active site in the full-length enzyme ( K m > 0.5 M), while retaining the ability to be activated by L-Phe. Furthermore, recent nuclear magnetic resonance (NMR) and analytical ultracentrifugation studies establish that a PheH construct containing only the regulatory domain undergoes a monomer-dimer transition in the presence of L-Phe 28,29 and that two molecules of L-Phe bind at a canonical ACT-domain dimer interface.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Because we introduced the idea that an activated tetramer contains an ACT domain dimer and that this dimer interface is the site of allosteric Phe binding (12), several new studies have provided support for this concept (27)(28)(29). We suggest a model for the activated PAH tetramer (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies of the isolated regulatory domain of rat PheH (RDPheH) have established that this domain indeed binds phenylalanine (23)(24)(25). Moreover, elimination of phenylalanine binding in the active site does not prevent the conformational change associated with phenylalanine activation, consistent with an allosteric site separate from the active site (26).…”
mentioning
confidence: 99%